A Companion to African Rhetoric - Ige, Segun; Motsaathebe, Gilbert; Ochieng, Omedi (Lexington Books, 2022)
A Companion to African Rhetoric, edited by Segun Ige, Gilbert Motsaathebe, and Omedi Ochieng, presents the reader with different perspectives on African rhetoric mostly from Anglophone sub-Saharan Africa and the Diaspora. The African, Afro-Caribbean, and African American rhetorician contributors conceptualize African rhetoric, examine African political rhetoric, analyze African rhetoric in literature, and address the connection between rhetoric and religion in Africa. They argue for a holistic view of rhetoric on the continent.